Formulation and Evaluation of Antibacterial and Antioxidant Polyherbal Lotion - Gyawali, Rajendra; Paudel, Nira; Shrestha, Sahana; Silwal, Ashok (Journal of Institute of Science and Technology, 2016)
There is increased scientific evidence that plants possess a vast and complex arsenal of active ingredients which have the ability to calm or smooth the skin as well as restore actively, heal and protect the skin. The present work deals with the development and evaluation of the poly herbal lotion containing Trigonella foenum-graecum, Citrus lemon, Matricaria chamomilla and Cymbopogon citrates. Different types of formulations oil in water (O/W) herbal lotions namely F1 to F13 were formulated by incorporating different concentrations of stearic acid and Triethanolamine. Formulation of Triethanolamine and stearic acid was optimized as 2.52:9.35. The prepared lotion was evaluated for its antimicrobial, antioxidant and pharmaceutical parameters. The lotion formulation showed no redness, edema, inflammation and irritation during sensitivity test indication that it is safe to use. Stability studies of the lotion showed that the lotion was stable after three months. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, Page: 148-156